The Review Book Of “Sacha Inchi : a Rich Nutrient Superfood from Amazon.” by Tresno Saras, Tiram Media Publisher, 2023 - Ningrat, R. Gamar Pratama Kusuma; Pamungkas, Bayu (Badan Kemitraan Inovasi dan Kewirausahaan Universitas Galuh, 2024)
This book was published by Tresno Saras, Tiram Publisher, 2023 with 32 pages. In the review of this book, the author discusses several chapters, namely Introduction to Sacha Inchi, Health Benefits of Sacha Inchi, Use of Inchi in Culinary, and Business Potential of Sacha Inchi. Some of the many discussions in this book are the history and culture of using Sacha Inchi, how to process Sacha Inchi into healthy food and drink products, and the potential for developing Sacha Inchi as a raw material for cosmetics and pharmaceuticals. Sacha Inchi, otherwise known as Inca beans or Inca Peanut, is a plant native to South America that grows well in the Amazon Region.